Managing Customer Citizenship Behavior in Aviation Sector Through Relational Benefits: Mediating Role of Relationship Quality - Hassan, Shahzad; Suki, Norazah Mohd (Frontiers in Psychology, 2022)
The aim of this research is to investigate the mediating role of relationship quality in the relationship between relational benefits and customer citizenship behavior. Data were gathered through a systematic sampling from 334 passengers. A Survey technique was used to collect the data from respondents from multiple airports. Data were analyzed through partial least square structural equation modeling (PLS-SEM) using SmartPLS 3.3. The results of the study reveal that altruistic benefits, confidence, and self-expression benefits have a positive relationship with relationship quality while socialization benefits have a non-significant relationship with relationship quality. Similarly, relationship quality mediates the relationship between altruistic benefits, confidence and self-expression benefits, and customer citizenship behavior while relationship quality does not mediate the relationship between socialization benefits and customer citizenship behavior. This study uncovers the relational benefits and its role in the generation of customer citizenship behavior in the aviation sector and the role of relationship quality that could help managers to cultivate the benefits of customer citizenship behaviors.